2008
DOI: 10.1093/rpd/ncn092
|View full text |Cite
|
Sign up to set email alerts
|

High-energy response of the PRESCILA and WENDI-II neutron rem meters

Abstract: WENDI-II was designed at the Los Alamos National Laboratory (LANL) specifically as a wide-range rem meter, suitable for applications at particle accelerators, with response extension to 5 GeV. PRESCILA was also designed at LANL, mainly as a lightweight alternative to traditional rem meters, but has shown excellent response characteristics above 20 MeV. This Note summarises measurements performed over a span of 4 y to characterise the high-energy neutron response (>20 MeV) of these meters to several hundred mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…The threshold for n/g discrimination was set as a default value; the negligibly low sensitivities to g-rays were confirmed for both monitors using 60 Co and 137 Cs source g-rays. The detail dosimetric properties of NCN1 and WENDI-II are introduced by Nakane et al (2004), Olsher et al (2000), and Olsher and McLean (2008), respectively. These two monitors were tested to measurements onboard a business jet aircraft near Japan (Yasuda et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…The threshold for n/g discrimination was set as a default value; the negligibly low sensitivities to g-rays were confirmed for both monitors using 60 Co and 137 Cs source g-rays. The detail dosimetric properties of NCN1 and WENDI-II are introduced by Nakane et al (2004), Olsher et al (2000), and Olsher and McLean (2008), respectively. These two monitors were tested to measurements onboard a business jet aircraft near Japan (Yasuda et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Below 0.1 and over 100 MeV, the instrument overestimates the H*(10) value. Important for this work is the fact that in the neutron energy range from 10 to 100 MeV, there is underestimation, with minimum value of about 0.5 in the range from about 15 to about 40 MeV [29,30]. Monte Carlo simulations of the proton therapy facility [31] have shown that about 70% of total H*(10) value is due to neutrons of energy from the range between 10 and 30 MeV.…”
Section: Resultsmentioning
confidence: 99%
“…Tungsten or tungsten carbide (WC) powder is added to a polyethylene moderator for the purpose of generating spallation neutrons in tungsten nuclei and thus enhance the high-energy response of the meter beyond 8 MeV. Tungsten's absorption resonance structure below several keV was also found to be useful in contouring the meter's response function [29,30]. NM2B is a moderated BF 3 proportional counter, whose response is considered acceptable for neutron energies between thermal limits and ~10 MeV.…”
Section: Methodsmentioning
confidence: 99%
“…It consists of a 3 He proportional counter surrounded by a cylindrical polyethylene moderator assembly and a layer of tungsten powder. This additional layer of high-Z material enhances the detector response to high-energy neutrons via inelastic scattering interactions [13,14]. The geometry of the detector is shown in Figure 7.…”
Section: Thermo Scientific Fht 752 (Biorem)mentioning
confidence: 99%